Can Emerging Market Central Banks Bail Out Banks? : A+L4848 Cautionary Tale From Latin America - Jacome H., Luis I. (IMF Working Papers; Working Paper ;, 2011)
This paper investigates whether developing and emerging market countries can implement monetary policies similar to those used by advanced countries during the recent global crisis - injecting significant amounts of money into the financial system without facing major short-run adverse macroeconomic repercussions. Using panel data techniques, the paper analyzes episodes of financial turmoil in 16 Latin America during 1995-2007. The results show that developing and emerging market countries should be cautious because injecting money on a large scale into the financial system may fuel further macroeconomic instability, increasing the chances of simultaneous currency crises.